Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2349/biij.3.1.e40
|View full text |Cite
|
Sign up to set email alerts
|

A review on the clinical implementation of respiratory-gated radiation therapy

Abstract: Respiratory-gated treatment techniques have been introduced into the radiation oncology practice to manage target or organ motions. This paper will review the implementation of this type of gated treatment technique where the respiratory cycle is determined using an external marker. The external marker device is placed on the abdominal region between the xyphoid process and the umbilicus of the patient. An infrared camera tracks the motion of the marker to generate a surrogate for the respiratory cycle. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
(19 reference statements)
0
34
0
Order By: Relevance
“…The differences for gating were ≤1.8 mm. Saw et al reported that differences in isodose levels between the measured and planned dose distribution should be within 3.0 mm in the high-dose region using respiratory-gated IMRT delivery [7]. The International Commission on Radiation Units and Measurement report 42 has recommended that the distance-to-agreement for the high dose region was ≤2.0 mm [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences for gating were ≤1.8 mm. Saw et al reported that differences in isodose levels between the measured and planned dose distribution should be within 3.0 mm in the high-dose region using respiratory-gated IMRT delivery [7]. The International Commission on Radiation Units and Measurement report 42 has recommended that the distance-to-agreement for the high dose region was ≤2.0 mm [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported the quality assurance (QA) for respiratory-gated RT using an external signal [7] [8]. Our group has aimed to perform the respiratory-gated RT using the fiducial marker for lung cancer with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Adding gating (beam holds) to VMAT increases the complexity further. Therefore it is important to evaluate the feasibility and the dosimetric accuracy of the gated VMAT before its clinical use (1,5) . The gamma agreement index in table 1 does not provide any clinically relevant information about the results (13) , whereas COMPASS system provides the signi-icance of error in PTV and as well as in OAR's (14)(15)(16)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…These treatment techniques target radiation doses precisely to the shape of tumors, reducing toxicity and side-effects. But for tumors in the thorax and abdomen region, respiratory motion is a limiting factor, which will degrade the effectiveness of conformal radiotherapy (1,2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation